Melbourne scenes and buildings (1970)
Photographs of Melbourne streets, monuments, views and buildings.
Title devised by cataloguer from material.
Condition: Faded.
Donated by Paul Street, 1994.
Keywords: Monuments -- Victoria -- Melbourne -- Photographs; Streets -- Victoria -- Melbourne -- Photographs; Melbourne (Vic.) -- Buildings, structures, etc. -- Photographs; Melbourne (Vic.) -- 20th century -- Photographs